Patients with cirrhosis and SBP: Increase in multidrug‐resistant organisms and complications. (21st January 2020) - Li, Hanwei; Wieser, Andreas; Zhang, Jiang; Liss, Ingrid; Markwardt, Daniel; Hornung, Roman; Neumann‐Cip, Anna C.; Mayerle, Julia; Gerbes, Alexander; Steib, Christian J.
Abstract: Background: Spontaneous bacterial peritonitis (SBP) is a serious complication in patients with liver cirrhosis. In recent years, it has been postulated that the rate of multidrug‐resistant organisms (MDROs) is increasing, especially in nosocomial SBP patients. Aim of the present work was to investigate this hypothesis and its possible clinical consequences. Materials and methods: One hundred and three culture‐positive patients between 2007 and 2014 were compared with 81 patients between 2015 and 2017, to study the change of microbiological profiles and their clinical consequences. The cirrhosis patients with bacterascites requiring treatment were included as well. Results: The most prevalent Gram‐negative bacteria isolated from ascites were Enterobacterales (31.6%) and in Gram‐positive pathogens Staphylococci (22.8%). There was a significant increase in MDROs (22.3% ICU 40.7%, P = .048), accompanied by an increased incidence of sepsis (from 21.4% to 37.0%, P = .021), hepatorenal syndrome (from 40.8% to 58.0%, P = .007) and the need of catecholamine therapy (from 21.4% to 38.8%, P = .036). Nosocomial origin correlated with higher MDRO proportion, more complications and lower antimicrobial susceptibility rates in 12 commonly used antibiotics. MDROs were confirmed as an isolated predictor for inpatient mortality and complications in multivariable logistic regression. Conclusions: The feeling in clinical practice that MDROs have increased in the last 11 years could be confirmed in our study in Munich, Germany. Nosocomial SBP correlated with significantly higher MDRO rates (nearly 50%) and complication rates. In our opinion, an antibiotic combination with comprehensive effect should be taken into account in nosocomial SBP patients in this region.